2019
DOI: 10.2147/ca.s207446
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Single-Centre Review of Transfusion Practices and Blood Wastage in Liver Transplantation</p>

Abstract: Background: Liver transplantation is associated with massive blood loss due to a combination of coagulopathy, portal hypertension, and multiple vascular transection and anastomoses. Multiple blood transfusions over a short time frame may result in significant blood and component wastage due to over-ordering of blood products and component time expiry. Blood wastage in the setting of liver transplantation is yet to be reviewed. We reviewed transfusion practices during liver transplantation and audited blood com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Limited data are available related to blood product wastage in the setting of liver transplant surgery. A retrospective study at one center that analyzed 181 liver transplant cases over a 1‐year period reported an overall blood wastage rate of 4.6% (142 total wasted units), with plasma showing the highest rate of wastage at 8.6%, mostly due to expiration after not being transfused 14 . Liver transplant surgeries impact blood bank operations in multiple ways, including the need for more staff and inventory on hand 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited data are available related to blood product wastage in the setting of liver transplant surgery. A retrospective study at one center that analyzed 181 liver transplant cases over a 1‐year period reported an overall blood wastage rate of 4.6% (142 total wasted units), with plasma showing the highest rate of wastage at 8.6%, mostly due to expiration after not being transfused 14 . Liver transplant surgeries impact blood bank operations in multiple ways, including the need for more staff and inventory on hand 12 …”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study at one center that analyzed 181 liver transplant cases over a 1-year period reported an overall blood wastage rate of 4.6% (142 total wasted units), with plasma showing the highest rate of wastage at 8.6%, mostly due to expiration after not being transfused. 14 Liver transplant surgeries impact blood bank operations in multiple ways, including the need for more staff and inventory on hand. 12 As blood is a finite resource and shortages are more commonplace during the COVID-19 pandemic, liver transplant and PBM programs must make a concerted effort to conserve blood whenever possible.…”
Section: Discussionmentioning
confidence: 99%